Quinazolinone-based rhodanine-3-acetic acids as potent aldose reductase inhibitors: Synthesis, functional evaluation and molecular modeling study. Issue 20 (15th October 2017) - El-sayed, Sherihan; Metwally, Kamel; El-Shanawani, Abdalla A.; Abdel-Aziz, Lobna M.; El-Rashedy, Ahmed A.; Soliman, Mahmoud E.S.; Quattrini, Luca; Coviello, Vito; la Motta, Concettina
Graphical abstract: Abstract: A series of quinazolinone-based rhodanine-3-acetic acids was synthesized and tested for in vitro aldose reductase inhibitory activity. All the target compounds displayed nanomolar activity against the target enzyme. Compounds3a, 3b, and3e exhibited almost 3-fold higher activity as compared to the only marketed reference drug epalrestat. Structure-activity relationship studies indicated that bulky substituents at the 3-phenyl ring of the quinazolinone moiety are generally not tolerated in the active site of the enzyme. Insertion of a methoxy group on the central benzylidene ring was found to have a variable effect on ALR-2 activity depending on the nature of peripheral quinazolinone ring substituents. Removal of the acetic acid moiety led to inactive or weakly active target compounds. Docking and molecular dynamic simulations of the most active rhodanine-3-acetic acid derivatives were also carried out, to provide the basis for further structure-guided design of novel inhibitors.